A general steam-assisted method for one-step synthesis of polymeric carbon nitride nanosheets with/without doping for efficient photocatalytic hydrogen evolution. Issue 3 (7th January 2020) - Shu, Zhu; Tan, Yigen; Zhou, Jun; Li, Tiantian; Chen, Jieyu; Chen, Donghang; Wang, Wenbin; Zhao, Zhengliang; Hu, Xiang
Abstract : A one-step steam-assisted method for preparing polymeric carbon nitride (PCN) nanosheets with/without doping for superior photocatalytic H2 evolution, using a green gas template, i.e. steam, decomposed from the recyclable steam source Mg(OH)2 . Abstract : Nano-structuring of polymeric carbon nitride (PCN) is an important strategy to improve its photocatalytic performance, while facile and green methods are scarce yet. Herein, we proposed a novel steam-assisted method to prepare holey PCN nanosheets in one step. Only a green gas template, i.e. steam, decomposed from the recyclable steam source Mg(OH)2 is needed for PCN nano-structuring. Moreover, in situ element doping of nano-structured PCN can be synchronously realized via this method. The holey PCN nanosheets and doped counterparts have boosted visible-light photocatalytic H2 evolution activities 12–35 times that of bulk PCN, benefitting from enlarged specific surface area, suppressed photogenerated electron–hole recombination and prolonged charge carrier lifetime. Steam-assisting may be a useful strategy for the facile and green synthesis of other nanosized PCN materials.